Фінансування освіти України з бюджетів різних рівнів в умовах війни - Тоцька, Олеся Леонтіївна; Титаренко, Іванна Олександрівна (Державна наукова установа «Інститут освітньої аналітики», 2023)
Статтю присвячено дослідженню особливостей фінансування освіти України з бюджетів різних рівнів в умовах війни. У роботі використано методи систематизації, порівняння, горизонтального та вертикального аналізу для вивчення абсолютних і відносних показників фінансування освіти з державного й місцевих бюджетів. Наведено вартісні показники зруйнованих і пошкоджених унаслідок війни активів сфери освіти та науки. Систематизовано й проведено порівняння показників видатків на освіту з бюджетів різних рівнів у 2020–2022 рр. Виявлено, що у 2022 р. видатки на освіту з Державного бюджету України були меншими, ніж у 2021 р., на 8,35 %, причому скорочення фінансування спостерігалося за всіма її видами, крім професійної (професійно-технічної) освіти, інших закладів і заходів у сфері освіти. Видатки на освіту з місцевих бюджетів у 2022 р. теж істотно знизилися – на 6,76 %, причому зменшення фінансування відбулося за всіма видами, за винятком професійної (професійно-технічної) освіти. За результатами порівняльного аналізу видатків на освіту з різних бюджетів, у місцевих бюджетах вони були більшими, ніж у держбюджеті: у 2020 р. – у 3,77 раза; у 2021 р. – у 3,90 раза; у 2022 р. – у 3,97 раза. Рекомендовано закладам освіти всіх рівнів здійснювати диверсифікацію джерел фінансування, а органам державної й місцевої влади – активно залучати кошти міжнародних організацій і благодійних фондів.

As a result of the russia’s invasion of Ukraine in February 2022, Ukraine’s education sector suffered serious destruction and losses. The purpose of the article is to study the features of financing in Ukrainian education from budgets of different levels in the context of war. To achieve this goal, the following tasks have been set: to analyze the value of destroyed and damaged assets of the education and science sector; to systematize and compare indicators of education expenditures from budgets of different levels in 2020–2022; to consider certain aspects of financing security and ensuring access to education for participants in the educational process. The following research methods are used in the study: systematization, comparison, horizontal and vertical analysis. It is indicated that the number of destroyed and damaged educational facilities reached 3,170, with a total estimated damage of almost 9 billion USD. Higher, secondary and preschool education institutions suffered the greatest losses. It is estimated that in 2022, compared to 2021, expenditures on education from the State Budget of Ukraine decreased by 8,35%, and from local budgets – by 6,76%. The data shows that in 2020–2022, the largest share of state budget expenditures on education was occupied by professional pre-higher and higher education (over 80%); in local budget expenditures – general secondary education (over 60%) and preschool education (over 17%). The following recommendations for educational institutions were formulated: to increase the supply of paid educational and research services; to increase the production of competitive products; to actively apply for grants from domestic and international organizations; to encourage benefactors to make voluntary contributions, etc. State and local authorities are recommended to pay special attention to financing the education sector.
Keywords: фінансування; освіта України; державний бюджет; місцеві бюджети; видатки; financing; education in Ukraine; state budget; local budgets; expenditures; 37.014.543(477)"364"